(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article provides an axiological analysis of the national socio-cultural and media-educational spaces of Kazakhstan. The authors of the article put forward a hypothesis about the relationship of spiritual values with other spheres of public life, about the possibility of the revival of the national spirit under their influence. The features of the functioning and development trends of the domestic media industry and media education are revealed. Education is shown as a historical phenomenon that is directly dependent on the level of development of society. In the article, the authors attempt, within the framework of social philosophy, to overcome the crisis of traditional foundations and principles of upbringing and education, to ensure the priority of universal human values in the hierarchy of educational goals. The authors come to the conclusion that the study of the modern educational landscape, the possibilities and ways of establishing media education in the sociocultural space will help understanding the education of the individual as the process of forming conscious independence, independence and human freedom in its tolerant and equal interaction with society and nature. Key words: education, upbringing philosophy, culture, media education, media industry, national spirit, mentality, informatization, digitalization, spiritual values.